The effect of alliance network diversity on multinational enterprise performance - Goerzen, Anthony; Beamish, Paul W. (Strategic Management Journal, 2005)
This paper examines the impact of alliance network diversity on multinational enterprise (MNE) economic performance. We consider competing hypotheses derived, alternatively, from transaction cost theory and network theory. Using a latent variable structural equation modeling approach on a sample of 580 large MNEs, we find that MNEs with more diverse alliance networks experience lower economic performance on average than those with less diverse alliance networks. Copyright © 2005 John Wiley & Sons, Ltd.